Strategi Peningkatan Pendapatan Usahatani Padi Sawah di Kota Tebing Tinggi - Saragih, Bahdan; Kuswardani, Retna Astuti; Hasibuan, Syahbudin (AGRISAINS: Jurnal Ilmiah Magister Agribisnis, 2019)
This study aims to determine the amount of income from lowland rice farming, determine the factors that affect the income of lowland rice farming and determine strategies for increasing the income of lowland rice farming in Tebing Tinggi City. The study was conducted in Tebing Tinggi City, North Sumatra Province which was carried out for 3 months, namely April - June 2017. The research approach was conducted descriptively through case studies. Data collection techniques carried out by observation, interviews, and filling out questionnaires. Data analysis methods used include R / C ratio analysis, regression analysis and Strengths, Weaknesses, Opportunities and Threats (SWOT) analysis. The results showed that lowland rice farming in Tebing Tinggi City was profitable with an R / C ratio of 2.54, the factors of production significantly affected the income of lowland rice farming in Tebing Tinggi City, and strategies in increasing the income of lowland rice farming in Tebing Tinggi City i.e. utilizing farmers' motivation to activate farmers' institutions in managing their farming, utilizing local government support and availability of vacant land to increase land area and access to capital, utilizing farmers' experience and using superior seeds to increase production and utilizing information and marketing technology that is easy to maintain economic value and meet consumer needs